CD73+ Mesenchymal Stem Cells Ameliorate Myocardial Infarction by Promoting Angiogenesis - Li, Qiong; Hou, Huifang; Li, Meng; Yu, Xia; Zuo, Hongbo; Gao, Jianhui; Zhang, Min; Li, Zongjin; Guo, Zhikun (Frontiers in Cell and Developmental Biology, 2021)
With multipotent differentiation potential and paracrine capacity, mesenchymal stem cells (MSCs) have been widely applied in clinical practice for the treatment of ischemic heart disease. MSCs are a heterogeneous population and the specific population of MSCs may exhibit a selective ability for tissue repair. The aim of our research was to adapt the CD73+ subgroup of adipose derived MSCs (AD-MSCs) for the therapy of myocardial infarction (MI). In this research, AD-MSCs were isolated from adipose tissue surrounding the groin of mice and CD73+ AD-MSCs were sorted using flow cytometry. To investigate the therapeutic effects of CD73+ AD-MSCs, 1.2 × 106 CD73+ AD-MSCs were transplanted into rat model of MI, and CD73– AD-MSCs, normal AD-MSCs transplantation served as control. Our results revealed that CD73+ AD-MSCs played a more effective role in the acceleration function of cardiac recovery by promoting angiogenesis in a rat model of MI compared with mixed AD-MSCs and CD73– AD-MSCs. Moreover, with the expression of CD73 in AD-MSCs, the secretion of VEGF, SDF-1α, and HGF factors could be promoted. It also shows differences between CD73+ and CD73– AD-MSCs when the transcription profiles of these two subgroups were compared, especially in VEGF pathway. These findings raise an attractive outlook on CD73+ AD-MSCs as a dominant subgroup for treating MI-induced myocardial injury. CD73, a surface marker, can be used as a MSCs cell quality control for the recovery of MI by accelerating angiogenesis.